2009
DOI: 10.1103/physrevd.79.084004
|View full text |Cite
|
Sign up to set email alerts
|

Barbero-Immirzi field in canonical formalism of pure gravity

Abstract: The Barbero-Immirzi (BI) parameter is promoted to a field and a canonical analysis is performed when it is coupled with a Nieh-Yan topological invariant. It is shown that, in the effective theory, the BI field is a canonical pseudoscalar minimally coupled with gravity. This framework is argued to be more natural than the one of the usual Holst action. Potential consequences in relation with inflation and the quantum theory are briefly discussed.Comment: 10 page

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
144
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(149 citation statements)
references
References 52 publications
5
144
0
Order By: Relevance
“…This anomaly leads to the inclusion of the Pontryagin density in an effective fermionic action [7]. Similarly, it has been recently found that LQG also leads to CS modified gravity when the Barbero-Immirzi parameter is promoted to a pseudo-scalar field in the presence of fermions [8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…This anomaly leads to the inclusion of the Pontryagin density in an effective fermionic action [7]. Similarly, it has been recently found that LQG also leads to CS modified gravity when the Barbero-Immirzi parameter is promoted to a pseudo-scalar field in the presence of fermions [8,9,10,11,12].…”
Section: Introductionmentioning
confidence: 79%
“…This anomaly leads to the inclusion of the Pontryagin density in an effective fermionic action [7]. Similarly, it has been recently found that LQG also leads to CS modified gravity when the Barbero-Immirzi parameter is promoted to a pseudo-scalar field in the presence of fermions [8,9,10,11,12].The signature of CS modified gravity is the enhancement of gravitational parity asymmetry, which in particular leads to frame-dragging modifications [13,14,15]. In GR, the gravitomagnetic sector of the metric couples to the spin and the orbital angular momentum of gravitating systems, leading to corrections in their orbital evolution, such as precession of the orbital plane.…”
mentioning
confidence: 84%
“…The Pontryagin term in the action is involved in anomaly cancellation [30]. Such a term also appears naturally in heterotic superstring theory [30][31][32] and loop quantum gravity [33][34][35]. Dynamical CS gravity also arises naturally in effective field theories of inflation [36].…”
Section: Introductionmentioning
confidence: 99%
“…However, when torsion is present (for instance, when it is generated by fermions or a spacetime-dependent Barbero-Immirzi field [18][19][20][21][22]), it is natural to include it explicitly in the fundamental action, so that the Holst term is completed by a torsion-torsion piece to form the Nieh-Yan invariant [17,23]. There are several other reasons why to prefer the latter alternative.…”
Section: Ij µmentioning
confidence: 99%